Ramadhan Star Camp (RSC): Learning Astronomy for Kids - Hamdani, Fahmi Fatwa Rosyadi Satria (Universitas Negeri Medan, 2022)
Astronomy is a science that persons who like it very little. Most assume that it contains more astronomical calculations are quite complicated elements. Even now, these calculations can be solved with some simple program that can be applied easily. Learning astronomy would be more pronounced if done early, especially for children, such as Ramadhan Star Camp (RSC) at Imahnoong Observatory. The agenda packed with “eduwisata” concept makes children don’t feel bored when presented celestial objects, and other astronomical instruments, also to provide practical astronomy, alteration of the mindset that learning is not difficult. Descriptive analysis method used in this paper, which the data obtained from the questionnaires given to the participants, then processed, classified, and at the final stage concluded. Finally, most of the members are very pleased with the RSC, and they can learn astronomy practice, combined with a series of exciting and fun activities in the concept of “eduwisata”